Are We Neglecting Nontuberculous Mycobacteria Just as Laboratory Contaminants? Time to Reevaluate Things. (21st June 2018) - Sharma, Pooja; Singh, Digvijay; Sharma, Kusum; Verma, Santwana; Mahajan, Sanjay; Kanga, Anil
Abstract : Objectives . Nontuberculous mycobacteria (NTM) incidences are on the rise worldwide, including the tuberculosis endemic areas. They should be identified rapidly to the species level and should be carefully differentiated as contamination, colonization, or disease. This study was aimed at determining the prevalence and clinicoepidemiological profile of mycobacteriosis cases. Materials and Methods . Cultures were made on liquid and solid media. NTM were identified by polymerase chain reaction (PCR) restriction analysis (PRA) and gene sequencing. Data was analyzed using Epi-info 7. Results . Out of the 1042 processed specimens, 16% were positive for M. tuberculosis complex and 1.2% for clinically significant NTM. M. intracellulare was the commonest species isolated. NTM were treated mainly on outdoor basis (92%), involving more extrapulmonary system (62%) and higher age-group of 41-60 years (69%). No significant factor was seen to be associated clinically, radiologically, and biochemically with the NTM infections. Conclusions . Our study highlights the importance of early diagnosis and differentiation among Mycobacterium tuberculosis and NTM so that these NTM are not underestimated in routine diagnostic procedures merely as environmental or laboratory contaminants.